Role and importance of high fiber in diabetes management in India. Issue 5 (May 2022) - Saboo, Banshi; Misra, Anoop; Kalra, Sanjay; Mohan, V.; Aravind, S.R.; Joshi, Shashank; Chowdhury, Subhankar; Sahay, Rakesh; Kesavadev, Jothydev; John, Mathew; Kapoor, Nitin; Das, Sambit; et al.
Abstract: Background & aims: India is facing a triple burden of pre-diabetes, diabetes, and obesity. Unhealthy eating habits and physical inactivity have been linked to the onset and progression of type 2 diabetes mellitus (T2DM). Despite dietary recommendations, individuals consume inadequate amounts or unsuitable type of dietary fiber (DF) which needs correction. An Expert group attempted to review and report on the role and importance of high DF in the management of T2DM and offer practical guidance on high fiber use in daily diet. Methodology: Twelve diabetologists and two expert dietitians from India were chosen to ensure diversity of the members both in professional interest and cultural background. The authors convened virtually for one group meeting and actively participated in a detailed discussion. Multiple reviews of the draft document followed by focused teleconference calls & email helped to reach consensus on final recommendations between Aug 2021 and Dec 2021. Results: Evidence has shown that medical nutrition therapy (MNT) is a valuable approach and an essential component of T2DM prevention and management. Studies have shown that fiber rich diabetes nutrition (FDN) has multi-systemic health benefits, including, improvement in glycemic control, reduction in glucose spikes, decrease in hyperinsulinemia, improvement in plasma lipid concentrations and weight management in T2DM patients. Conclusion: A high fiber diet is vital for people with diabetes and associated conditions. Increasing fiber intake, preferably through food or through dietary supplement, may help. Fiber rich diabetes nutrition (FDN) is recommended in order to prevent and manage T2DM. Highlights: Unhealthy diet and physical inactivity have led to an increase in prevalence of T2DM. Fiber rich diabetes nutrition plays an important role in management of T2DM. Increase fiber intake, preferably of the soluble type, for T2DM patients. Intake of both dietary and supplementary forms are useful. 25–40 gm of fiber per day is recommended.